Search for antibacterial activity in a number of new S-derivatives (1,2,4-triazole-3(2H)-yl)methyl)thiopyrimidines - Karpenko, Yu. V.; Panasenko, O. I.; Карпенко, Юрій Вікторович; Панасенко, Олександр Іванович; Карпенко, Ю. В.; Панасенко, А. И. (Запорізький державний медичний університет, 2021)
The relevance of the study of 1,2,4-triazole derivatives with pyrimidine fragment is due to the synthesis of potential broad-spectrum antibacterial drugs, low molecular weight inducers of interferon, and antitumor agents, search for molecular descriptors of their structure, important for establishing patterns “structure – biological activity”. The aim of the work is a computer search for the antibacterial action of new hybrids of 1,2,4-triazole-3(2H)-thiol with a pyrimidine fragment in relation to 5 test cultures, to establish the dependence of “structure – action”. Materials and methods. For an in-depth study of the antibacterial activity of derivatives of 1,2,4-triazole-3(2H)-thiol hybrids with a pyrimidine fragment, 4 test cultures of museum strains of gram-positive, gram-negative bacteria and one species of fungi were selected. In silico studies were performed using regression and classification QSAR models. Results. Derivatives of 1,2,4-triazole-3(2H)-thiol hybrids with a pyrimidine moiety showed high antibacterial activity against gramnegative microorganisms (E. coli, P. aeruginosa). The obtained experimental results allowed to establish not only the role of the main structural features of the compounds in the manifestation of antimicrobial properties, but also to evaluate the effectiveness of the created classification and regression QSAR models. Based on the presented parameters for individual predictive QSAR models, it is possible to conclude about the effectiveness, stability and feasibility of using these models to search for new S-derivatives (1,2,4-triazole-3(2H)-yl) methyl)thiopyrimidines as promising antimicrobial agents. Conclusions. It was found that the studied derivatives of hybrids of 1,2,4-triazole-3(2H)-thiol with a pyrimidine fragment showed high antibacterial activity against gram-negative microorganisms. The developed QSAR classification models based on the percentage of correctly predicted compounds (70 %) are the most effective in comparison with regression (50 %) for the search for new antimicrobial agents in a number of derivatives of hybrids 1,2,4 triazole-3(2H)-thiol with pyrimidine fragment . Актуальність дослідження похідних 1,2,4-тріазолу з піримідиновим фрагментом зумовлена синтезом потенційних антибактеріальних лікарських препаратів широкого спектра дії, низькомолекулярних індукторів інтерферону та протипухлинних агентів, пошуком молекулярних дескрипторів їхньої структури, важливих для встановлення закономірностей «структура – біологічна активність». Мета роботи – комп’ютерний пошук антибактеріальної дії нових гібридів 1,2,4-тріазол-3(2Н)-тіолів із піримідиновим фрагментом щодо 5 тест-культур, встановити залежність «структура – дія». Матеріали та методи. Для поглибленого вивчення антибактеріальної дії похідних гібридів 1,2,4-тріазол-3(2Н)-тіолу з піримідиновим фрагментом обрали 4 тест-культури музейних штамів грампозитивних і грамнегативних бактерій та один вид грибів. In silico дослідження виконували за допомогою регресійних і класифікаційних QSAR-моделей. Результати. Похідні гібридів 1,2,4-тріазол-3(2Н)-тіолу з піримідиновим фрагментом показали високу антибактеріальну активність щодо грамнегативних мікроорганізмів (E. сoli, Р. aeruginosa). Експериментальні результати дали можливість не тільки встановити роль основних структурних особливостей сполук у прояві антимікробних властивостей, але й оцінити ефективність створених класифікаційних і регресійних QSAR моделей. На підставі наведених параметрів для індивідуальних QSAR моделей для прогнозу можна зробити висновок про ефективність, стабільність, доцільність використання цих моделей для пошуку нових S-похідних (1,2,4-тріазол-3(2H)-іл)метил)тіопіримідинів як перспективних антимікробних агентів. Висновки. Встановили, що досліджувані похідні гібриди 1,2,4-тріазол-3(2Н)-тіолу з піримідиновим фрагментом показали високу антибактеріальну активність щодо грамнегативних мікроорганізмів. Розроблені класифікаційні QSAR моделі за показником відсотка правильно прогнозованих сполук (70 %) вважаємо найефективнішими порівняно з регресійними (50 %) для пошуку нових антимікробних агентів у ряду похідних гібридів 1,2,4тріазол-3(2Н)-тіолу з піримідиновим фрагментом. Актуальность исследования производных 1,2,4-триазола с пиримидиновым фрагментом обусловлена синтезом потенциальных антибактериальных лекарственных препаратов широкого спектра действия, низкомолекулярных индукторов интерферона и противоопухолевых агентов, поиском молекулярных дескрипторов их структуры, важных для установления закономерностей «структура – биологическая активность». Цель работы – компьютерный поиск антибактериального действия новых гибридов 1,2,4-триазол-3(2Н)-тиолов с пиримидиновым фрагментом относительно 5 тест-культур, установить зависимость «структура – действие». Материалы и методы. Для углубленного изучения антибактериального действия производных гибридов 1,2,4-триазол-3(2Н)-тиола с пиримидиновым фрагментом отобрали 4 тест-культуры музейных штаммов грамположительных и грамотрицательных бактерий и один вид грибов. In silico исследования проведены с помощью регрессионных и классификационных QSAR-моделей. Результаты. Производные гибридов 1,2,4-триазол-3(2Н)-тиола с пиримидиновым фрагментом показали высокую антибактериальную активность в отношении грамотрицательных микроорганизмов (E. сoli, Р. aeruginosa). Экспериментальные результаты позволили не только установить роль основных структурных особенностей соединений в проявлении антимикробных свойств, но и оценить эффективность созданных классификационных и регрессионных QSAR моделей. На основе представленных параметров для индивидуальных прогнозирующих QSAR моделей можно сделать вывод об эффективности, стабильности и целесообразности использования данных моделей для поиска новых S-производных (1,2,4-триазол-3(2H)-ил)метил)тиопиримидинов как перспективных антимикробных агентов . Выводы. Установили, что исследуемые производные гибриды 1,2,4-триазол-3(2Н)-тиола с пиримидиновым фрагментом показали высокую антибактериальную активность в отношении грамотрицательных микроорганизмов. Разработанные классификационные QSAR модели с показателем процента верно прогнозируемых соединений (70 %) представляются наиболее эффективными по сравнению с регрессионными (50 %) для поиска новых антимикробных агентов в ряду производных гибридов 1,2,4 триазол-3(2Н)-тиола с пиримидиновым фрагментом.
Пошук антибактеріальної активності в ряду нових S-похідних (1,2,4-тріазол-3(2H)-іл)метил)тіопіримідинів
Поиск антибактериальной активности в ряду новых S-производных (1,2,4-триазол-3(2H)-ил)метил)тиопиримидинов
Карпенко Ю. В. - ORCID ID: 0000-0002-4390-9949; Панасенко О. І. - ORCID ID: 0000-0002-6102-3455.
Keywords: 1,2,4-triazole; pyrimidines; antibacterial activity; QSAR; 1,2,4-триазол; піримідин; антибактеріальна активність; класифікаційні QSAR моделі; регресійні QSAR моделі; пиримидин; антибактериальная активность; классификационные QSAR модели; регрессионные QSAR модели